1978
DOI: 10.2466/pr0.1978.42.2.419
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Fear of Death and Level of Self-Esteem in College Students

Abstract: Self-esteem and death anxiety instruments were administered to a total of 383 undergraduates; black and white, males and females were included in the sample. Consistent with previous data, higher scores on death anxiety were shown by female subjects. Black males displayed significantly higher self-esteem scores. An analysis of subgroups low and high in self-esteem produced support for a negative relationship between level of self-esteem and death anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
5
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 6 publications
5
5
0
2
Order By: Relevance
“…More specifically, the women had higher death anxiety scores than did the men. This significant difference corroborates a number of previous reports that have shown that women had higher expressed fear of death than did men (e. g., Buzzanga et al, 1989;Davis, Bremer, Anderson, & TramiU, 1983;Davis, Martin, Wilee, & Voorhees, 1978;Koob & Davis, 1977;Sadowski, Davis, & Loftus-Vergari, 1979;Templer, Lester, & Ruff, 1974;Tramill, Davis, Bremer, Dudeck, & Elsbury, 1982;Tramill, Kleinhammer-Tramill, Davis, Parks, & Alexander, 1984).…”
Section: Resultssupporting
confidence: 80%
“…More specifically, the women had higher death anxiety scores than did the men. This significant difference corroborates a number of previous reports that have shown that women had higher expressed fear of death than did men (e. g., Buzzanga et al, 1989;Davis, Bremer, Anderson, & TramiU, 1983;Davis, Martin, Wilee, & Voorhees, 1978;Koob & Davis, 1977;Sadowski, Davis, & Loftus-Vergari, 1979;Templer, Lester, & Ruff, 1974;Tramill, Davis, Bremer, Dudeck, & Elsbury, 1982;Tramill, Kleinhammer-Tramill, Davis, Parks, & Alexander, 1984).…”
Section: Resultssupporting
confidence: 80%
“…However, the lack of a relation between interpersonal flexibility and death anxiety was surprising and suggests that further research on this clustering of factors is needed. The present data also replicate two previous findings: (1) the negative relationship between self-esteem and death anxiety (Buzzanga, Miller, Peme, Sander, & Davis, 1989;Davis, Martin, Wilee, & Voorhees, 1978), and (2) the display of higher levels of death anxiety by women than by men (Koob & Davis, 1977;Sadowski, Davis, Loftus-Vergari, 1979;Tramill, Kleinhammer-Tramill, Davis, Parks, & Alexander, 1984). The finding that men and women did not differ on level of self-esteem contradicts earlier reports (Davis et al, 1978), but corroborates more recent data (Buzzanga et al, 1989).…”
Section: Resultssupporting
confidence: 81%
“…Other studies using global measures of fear of death have found that African Americans report higher levels of anxiety than Caucasians across diverse socioeconomic levels (e.g., Dodd & Mills, 1985;Myers, Wass, & Murphey, 1980). However, other research using multiethnic samples has not identified race as a significant predictor of death concerns (e.g., Bengtson et al, 1977;Davis, Martin, Wilee, & Voorhees, 1978). Use of a multidimensional approach to assessing death-related fears could contribute to more precise understanding of the death concerns of particular subgroups of older respondents.…”
Section: Death Anxiety and Ethnicity In The Elderlymentioning
confidence: 96%